Paediatric nephrology: The last 50 years. (24th December 2014) - Kausman, Joshua Y; Powell, Harley R
Abstract In 1965, the specialty of paediatric nephrology was in its infancy. Following the development of a landmark collaborative research study, the International Study of Kidney Disease in Childhood in the mid‐1960s, the first specialist societies were formed: the European Society of Pediatric Nephrology in 1967 and the American Society of Pediatric Nephrology in 1969. The extraordinary improvements in care delivered to children with kidney disease over the past 50 years are too broad to cover in any one paper. They traverse the spectrum of diagnosis, classification, therapeutics, social well‐being and transition to adult care. We have selected four case scenarios to highlight these changes in key areas of paediatric nephrology: post‐streptococcal glomerulonephritis, nephrotic syndrome, haemolytic uraemic syndrome and neonatal dialysis and childhood transplantation.